2022
DOI: 10.1039/d2ew00524g
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: environment-specific auxiliary substrates tailored for effective cometabolic bioremediation of 1,4-dioxane

Abstract: Cometabolic bioremediation is trending for the treatment of 1,4-dioxane (dioxane) and other emerging contaminants to meet stringent regulatory goals (e.g., <10 µg/L) since the biodegradation activities can be fueled by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…For instance, enhanced biodegradation of the pollutant 1,4-dioxane has previously been reported in the Arctic and American deep groundwater samples in the presence of different alcohols, which caused an overall boost in biomass (Deng et al, 2022;Li et al, 2010). In contrast, the presence of Group 2 auxiliary substrates, which possibly share the carbofuran pathway, might, over the long term, enhance carbofuran biodegradation kinetics through enhanced pathway expression or pathway induction (Deng et al, 2022;Sun et al, 2016). Slower degradation of Group 2 auxiliary substrates compared to carbofuran indicates that competitive inhibition does not play a role for carbofuran biodegradation in the presence of Group 2 auxiliary substrates.…”
Section: Biodegradation Mechanisms Of the Different Transformation Gr...mentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, enhanced biodegradation of the pollutant 1,4-dioxane has previously been reported in the Arctic and American deep groundwater samples in the presence of different alcohols, which caused an overall boost in biomass (Deng et al, 2022;Li et al, 2010). In contrast, the presence of Group 2 auxiliary substrates, which possibly share the carbofuran pathway, might, over the long term, enhance carbofuran biodegradation kinetics through enhanced pathway expression or pathway induction (Deng et al, 2022;Sun et al, 2016). Slower degradation of Group 2 auxiliary substrates compared to carbofuran indicates that competitive inhibition does not play a role for carbofuran biodegradation in the presence of Group 2 auxiliary substrates.…”
Section: Biodegradation Mechanisms Of the Different Transformation Gr...mentioning
confidence: 99%
“…In particular, auxiliary substrates that are degraded by the same pathway as OMPs can be beneficial for bioremediation purposes (Deng et al, 2022; Sun et al, 2016). Such substrates can induce and maintain the OMP biodegradation pathway and thus enhance biodegradation kinetics (Deng et al, 2022; Sun et al, 2016), when substrate competition for the degrading enzymes is minor (Rentz et al, 2004). For instance, a recent study found that dioxane biodegradation by Azoarcus sp.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations